2017
DOI: 10.2196/mhealth.8238
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea in Women: Study of Speech and Craniofacial Characteristics

Abstract: BackgroundObstructive sleep apnea (OSA) is a common sleep disorder characterized by frequent cessation of breathing lasting 10 seconds or longer. The diagnosis of OSA is performed through an expensive procedure, which requires an overnight stay at the hospital. This has led to several proposals based on the analysis of patients’ facial images and speech recordings as an attempt to develop simpler and cheaper methods to diagnose OSA.ObjectiveThe objective of this study was to analyze possible relationships betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…For instance, Lee et al reported that OSAS patients often exhibit broader and flatter mid- and lower-thirds of the face, accompanied by reduced maxillary and mandibular lengths [ 45 ]. Similarly, Tyan et al identified significant correlations between craniofacial measurements and the severity of OSAS [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lee et al reported that OSAS patients often exhibit broader and flatter mid- and lower-thirds of the face, accompanied by reduced maxillary and mandibular lengths [ 45 ]. Similarly, Tyan et al identified significant correlations between craniofacial measurements and the severity of OSAS [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Craniofacial soft tissue evaluation is another important aspect. 31 Many authors evaluated OSA patients by using photographic evaluation or the 3D surface scanning of the face. 32 , 33 Lee et al 32 suggested that patients with OSA showed a wider and flatter mid-third and lower-third of the face.…”
Section: Discussionmentioning
confidence: 99%
“…Tyan et al showed a significant correlation between craniofacial measurements (i.e., cervico-mental contour ratio, Face-width ratio, tragion-ramus-stomion angle) and AHI in OSA patients. 31 Liu et al described the craniofacial and cephalometric parameters observed in OSA patients, and their influence in OSA treatment with mandibular advancement devices. 34 The authors suggested two types of craniofacial and soft tissue shape of OSA patients: subjects with a forward maxilla, a small oropharynx, less erupted maxillary molars, small incisor overjet, and a small soft palate, and patients with maxilla retrusion, a larger oropharynx, a larger soft palate, and over-erupted maxillary molars.…”
Section: Discussionmentioning
confidence: 99%
“…In the first approach, using the existing training dataset a statistical model of the face is generated to fit test images. This approach, which is used in Tyan et al (2017) as an automatic annotation to predict OSA, has limitations in dealing with variations of the images (scale, pose, illumination, etc). In the second approach, face landmarks are localized by solving the regression problem which relates the features of the training datasets and their associated landmarks.…”
Section: Automatic Landmark Annotationmentioning
confidence: 99%
“…Such quantity provides a standard platform to evaluate the performance of classifications. In Tyan et al (2017) the same set of features and landmarks as Espinoza-Cuadros et al (2015) were automatically generated and used to predict OSA from facial features for female subjects, and a correlation between those features and AHI was shown. Although Espinoza-Cuadros et al (2015) and Tyan et al (2017) used the same landmarks, it is difficult to compare the performance of the automatic versus manual landmarking processes as different datasets were used.…”
Section: Introductionmentioning
confidence: 99%